Biosynthesis of gold and silver nanoparticles using emblica officinalis fruit extract, their phase transfer and transmetallation in an organic solution - Ankamwar, Balaprasad; Damle, C.; Ahmad, Absar; Sastry, M. (Journal of Nanoscience and Nanotechnology, 2005)
The design, synthesis and characterization of biologically synthesized nanomaterials have become an area of significant interest. In this paper, we report the extracellular synthesis of gold and silver nanoparticles using Emblica Officinalis (amla, Indian Gooseberry) fruit extract as the reducing agent to synthesize Ag and Au nanoparticles, their subsequent phase transfer to an organic solution and the transmetallation reaction of hydrophobized silver nanoparticles with hydrophobized chloroaurate ions. On treating aqueous silver sulfate and chloroauric acid solutions with Emblica Officinalis fruit extract, rapid reduction of the silver and chloroaurate ions is observed leading to the formation of highly stable silver and gold nanoparticles in solution. Transmission Electron Microscopy analysis of the silver and gold nanoparticles indicated that they ranged in size from 10 to 20 nm and 15 to 25 nm respectively. Ag and Au nanoparticles thus synthesized were then phase transferred into an organic solution using a cationic surfactant octadecylamine. Transmetallation reaction between hydrophobized silver nanoparticles and hydrophobized chloroaurate ions in chloroform resulted in the formation of gold nanoparticles.
Keywords: Biosynthesis; Nanomaterials; Phase transfer; Transmetallation